1977
DOI: 10.1346/ccmn.1977.0250604
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the Adsorption Mechanism of Acetamide and Polyacrylamide on to Clays

Abstract: Abstrac~While studying the retention of additives used in tertiary recovery of petroleum (waterflooding) on minerals present in a rock reservoir, an investigation has been undertaken into the adsorption mechanism of polyacrylamides on to clays. The adsorption of amides and polyacrylamides takes place exclusively on the external surfaces of the clay particles. The organic molecules are protonated on the surface and adsorbed by ionic forces. There is a linear relationship between the adsorption ratio and the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 33 publications
5
39
0
3
Order By: Relevance
“…This clay, named HYPER clay, is mixed with a polymeric solution containing the polymer and then dehydrated in an oven at 105°C to irreversibly adsorb the polymer to the clay surface. Dehydration at temperature higher than 60°C has been proven to enhance the irreversible adsorption of the polymer on the clay surface [87]. After HYPER clay treatment, the anionic polymer intercalates in the interlayer region between clay platelets (as demonstrated by XRD analysis by [23]).…”
Section: Clay Treated With Anionic Polymer and Dehydration (Hyper Clay)mentioning
confidence: 99%
See 2 more Smart Citations
“…This clay, named HYPER clay, is mixed with a polymeric solution containing the polymer and then dehydrated in an oven at 105°C to irreversibly adsorb the polymer to the clay surface. Dehydration at temperature higher than 60°C has been proven to enhance the irreversible adsorption of the polymer on the clay surface [87]. After HYPER clay treatment, the anionic polymer intercalates in the interlayer region between clay platelets (as demonstrated by XRD analysis by [23]).…”
Section: Clay Treated With Anionic Polymer and Dehydration (Hyper Clay)mentioning
confidence: 99%
“…On the other hand, Michaels and Morelos [63] suggested that adsorption is mainly conditioned by hydrogen bonding. A third possibility would originate from the interaction between polyvalent cations acting as crosslinking agents between the clay negative surface and the anionic polymer [87]. In the presence of salts and cations naturally present at the clay surface, the negative charges of the clay and the anionic polymer are shielded from one another allowing the polymer to coil and collapse on the clay surface [14].…”
Section: Clay Treated With Anionic Polymer and Dehydration (Hyper Clay)mentioning
confidence: 99%
See 1 more Smart Citation
“…Flokülasyon işlemine takiben 15 dk bekledikten sonra, dereceli pipet yardımıyla hava-sıvı ara yüzeyinin yaklaşık 4 cm derinlikten 20 ml numune alınıp bulanıklık değeri türbidimetre yardımıyla tespit edilmiştir. [19].…”
Section: Yöntemunclassified
“…Yüksek molekül ağırlığa sahip anyonik flokülantlar, sahip oldukları uzun hidrokarbon zincirleri vasıtasıyla tanelere tutunarak taneler arası köprü oluşturmak suretiyle flok meydana getirmektedirler. Kaolinit tipi kil minerallerinin bulunduğu sistemlerde ise yüzeylere hidrojen bağı ile tutunarak duraylı haldeki kolloidal taneciklerin duraysız olmasını sağlarlar [19,20].…”
Section: Yöntemunclassified